2005
DOI: 10.1002/ana.20670
|View full text |Cite
|
Sign up to set email alerts
|

Noise‐enhanced balance control in patients with diabetes and patients with stroke

Abstract: This work indicates that noise-based devices could ameliorate diabetic and stroke impairments in balance control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
306
4
11

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 320 publications
(333 citation statements)
references
References 67 publications
12
306
4
11
Order By: Relevance
“…Subsensory mechanical noise chips on the bottom of the feet reduce sway in clinical and typical populations (Priplata et al 2002(Priplata et al , 2003(Priplata et al , 2006. The explanation for this could be that noise increases somatosensory feedback from the feet.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Subsensory mechanical noise chips on the bottom of the feet reduce sway in clinical and typical populations (Priplata et al 2002(Priplata et al , 2003(Priplata et al , 2006. The explanation for this could be that noise increases somatosensory feedback from the feet.…”
Section: Discussionmentioning
confidence: 99%
“…The support for this is that mechanical noise can reduce sway both in people with peripheral and central deficits (Priplata et al 2003(Priplata et al , 2006, and SR is a mechanism that works both in somatosensory (Douglass et al 1993;Levin and Miller 1996) and auditory system signal transfer (Mangiore 2012). It should be explored whether auditory noise can reduce sway variability in people with instability due to central nervous system damage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Perry (2006) concluded that both vibratory and touch detection thresholds decline with age: The loss of cutaneous sensation correlated with an impaired control of balance and an increased likelihood of falling. Other authors showed that applying vibration (Dhruv et al 2002;Priplata et al 2003;Priplata et al 2006) or rotary plantar massages (Bernard-Demanze et al 2004) to the foot soles enhances both cutaneous sensation (Dhruv et al 2002) and balance control (Maurer et al 2001;Bernard-Demanze et al 2004). Placing a raised edge underneath the perimeter of the plantar foot surface also facilitates postural stability (Maki et al 1999).…”
Section: Introductionmentioning
confidence: 99%